2011
DOI: 10.1177/1548051810397368
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of Positive Psychological Constructs and Emotions on Stress, Anxiety, and Well-Being

Abstract: Two studies were conducted including one involving a longitudinal research design to understand better the influential role of the positive psychological capacities of hope, efficacy, optimism, resilience, as well as positive emotions on individual stress, anxiety, and well-being. Study 1 (N = 1,316) was conducted to validate a hypothesized relationship between the positive capacities and well-being. Next, in Study 2 (N = 172), data were collected from participants at 12 points in time over 4 months and random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 73 publications
5
59
0
9
Order By: Relevance
“…Thus, the correlation is positive with job satisfaction (Larson & Luthans, 2006;Luthans et al, 2008) and negative both with perceived ill health-indicating that the higher the psychological capital levels are, the better health they enjoy (as according to the anales de psicología, 2017, vol. 33, nº 3 (october) measure of health GHQ-12, the higher marks they got, the worse health perception they had) -and psychomatic symptoms, a result also in accordance with the previous findings Avey, Wernsing & Mhatre, 2011).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, the correlation is positive with job satisfaction (Larson & Luthans, 2006;Luthans et al, 2008) and negative both with perceived ill health-indicating that the higher the psychological capital levels are, the better health they enjoy (as according to the anales de psicología, 2017, vol. 33, nº 3 (october) measure of health GHQ-12, the higher marks they got, the worse health perception they had) -and psychomatic symptoms, a result also in accordance with the previous findings Avey, Wernsing & Mhatre, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have shown positive and negative connections between psychological capital and different work and organisational variables such as job satisfaction (Badran & Youssef-Morgan, 2015;Karatepe & Karadas, 2015;, organisational commitment (Larson & Luthans, 2006), engagement (Avey, Hughes, Norman & Luthans, 2008), efficacy , intention to leave the organisation (Avey, Luthans & Jensen, 2009;Schulz, Luthans & Messersmith, 2014), burnout (Cheung, Tang & Tang, 2011;Dinget al, 2015), and health and welfare in workers (Avey, Wernsing & Mhatre, 2011;Krasikova, Lester & Harms, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The relation between stress and optimism was one of the objectives of a study with 172 adults, which indicated, among the results, that the higher the optimism the lower was the stress caused by the daily work (23) . In Seoul, a study with 252 elderly ladies evaluated if optimism would be related with the subjective wellbeing and the meaning of life, observing that the more optimist elderly tend to give greater meaning to life, which contributes to increase the subjective wellbeing (24) .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, studies have shown that optimism is an effective measure for reduction of stress in different scenarios of evaluation (23,25) . In this study it was also found that optimism reduces stress in elderlies that care for elderlies and live with children.…”
Section: Discussionmentioning
confidence: 99%
“…Ademais, o despiste e a sinalização prematuras destes casos são também favoráveis numa visão económica, na medida em que permitem uma importante redução de custos na área da saúde. Por outro lado, parece plausível do ponto de vista teórico e prático apostar no desenvolvimento de capital psicológico do indivíduo, cujas várias implicações positivas na promoção do bem-estar do individuo foram já evidenciadas (Avey, Wernsing, & Mhatre, 2011). O capital psicológico respeita a um estado de desenvolvimento psicológico positivo constituído por quatro dimensões: autoeficácia, otimismo, esperança e resiliência e a sua relação com o distress psicológico em estudantes do ensino superior encontra-se descrita (Li-feng & Hua-li, 2009), tendo sido encontrado um efeito moderador do capital psicológico na experiência de distress psicológico (quanto mais forte a presença de constructos psicológicos associados ao capital, menor a experiência de DP).…”
Section: Estudo Das Validadesunclassified